GEOCHEMISTRY OF THE JELAI VOLCANICS FROM MOUNT RIAN EAST KALIMANTAN: Implications for the magma compositional gap - Sulistyawan, R.I H; Baharuddin, Baharuddin; Hartono, U (Jurnal Geologi dan Sumberdaya Mineral, 2013)
The Jelai volcanics are exposed at Mount Rian and the surrounding area, northeastern part of Kalimantan. Major, trace and rare earth element data are presented. The volcanics consist of basalt to andesite with silica content ranging from about 52 to 63.5 wt%. Fractional crystallization involving olivine, pyroxene, plagioclas, and magnetite may resposible for the geochemical variation in the volcanics. However, there is a silica gap about 5wt% between basaltic andesite and andesite. Two trends of fractionation are observed, i.e., the tholeiitic and calc-alkaline trends in the basaltic and andesitic magmas respectivelly. Precipitation of magnetite, as a new phase, in the andesitic magma might change the fractionation from tholeiitic to calc-alkaline trends. Initial crystallization of Fe-Ti magmentite, pyroxene and plagioclase, that produce a rapid compositional change in the residual basaltic andesite to andesite liquids over a small temperature interval would cause a compositional gap.Keyword : Mount Rian volcanics, geochemistry, compositional gapAbstrak